Lurasidone as a potential therapy for bipolar disorder - Woo YS (Dove Medical Press, 2013)
Young Sup Woo, Hee Ryung Wang, Won-Myong Bahk Department of Psychiatry, Yeouido St Mary's Hospital, The Catholic University of Korea, Seoul, Korea Abstract: Lurasidone is a benzisothiazol derivative and an atypical antipsychotic approved by the US Food and Drug Administration for the acute treatment of adults with schizophrenia (October 2010) and bipolar 1 depression (June 2013). Lurasidone has a strong antagonistic property at the D2, serotonin (5-HT)2A, and 5-HT7 receptors, and partial agonistic property at the 5-HT1A receptor. Lurasidone also has lower binding affinity for the α2C and 5-HT2C receptor. Lurasidone is rapidly absorbed (time to maximum plasma concentration: 1–3 hours), metabolized mainly by CYP3A4 and eliminated by hepatic metabolism. In two large, well-designed, 6-week trials in adult patients with bipolar 1 depression, lurasidone monotherapy and adjunctive therapy with mood stabilizers were significantly more effective than placebo at improving depressive symptoms assessed using the Montgomery–Åsberg Depression Rating Scale total score. In both trials, lurasidone also reduced the Clinical Global Impression–Bipolar Severity depression score to a greater extent than placebo. In these two trials, discontinuation rates due to adverse events in the lurasidone group were small (<7%) and were not different from those of the placebo group. The most common adverse events in the lurasidone group were headache, nausea, somnolence, and akathisia. The changes in lipid profiles, weight, and parameters of glycemic control were minimal, and these findings were in line with those observed in schizophrenia trials. Further active comparator trials and long-term tolerability and safety data in bipolar patients are required. Lurasidone may be an option for the management of depressive symptoms in patients with bipolar 1 disorder, and it may be considered as a treatment alternative for patients who are at high risk for metabolic abnormalities. Keywords: lurasidone, bipolar disorder, acute depression, metabolic